Incidence and prediction of invasive disease and nodal metastasis in preoperatively diagnosed ductal carcinoma in situ. Issue 5 (26th March 2014) - Osako, Tomo; Iwase, Takuji; Ushijima, Masaru; Horii, Rie; Fukami, Yasuyoshi; Kimura, Kiyomi; Matsuura, Masaaki; Akiyama, Futoshi
<x xml:space="preserve">Abstract</x> For breast cancer patients with a preoperative diagnosis of ductal carcinoma in situ (DCIS), sentinel lymph node (SN) biopsy has been proposed as an axillary staging procedure in selected patients with a higher likelihood of having occult invasive lesions. With detailed histological examination of primary tumors and molecular whole‐node analysis of SNs, we aimed to validate whether this selective application accurately identifies patients with SN metastasis. The subjects were 336 patients with a preoperative needle‐biopsy diagnosis of DCIS who underwent SN biopsy using the one‐step nucleic acid amplification assay in the period 2009–2011. The incidence and preoperative predictors of upstaging to invasive disease on final pathology and SN metastasis, and their correlation, were investigated. Of the 336 patients, 113 (33.6%) had invasive disease, and 6 (1.8%) and 17 (5.0%) had macro‐ and micrometastasis in axillary nodes respectively. Of the 113 patients with invasive disease, 4 (3.5%) and 9 (8.0%) had macro‐ and micrometastasis. Predictors of invasive disease included palpability, mammographic mass, and calcifications (spread >20 mm), and intraductal solid structure, but no predictor was found for SN metastasis. Therefore, even though occult invasive disease was found at final pathology, most of the patients had no metastasis or only micrometastasis in axillary nodes. Predictors of invasive disease and SN metastasis were not completely consistent, so the selective SN biopsy for patients with a higher risk of invasive disease may not accurately identify those with SN metastasis. More accurate application of SN biopsy is required for patients with a preoperative diagnosis of DCIS.